The role of molecular crowding in long-range metalloprotein electron transfer: Dissection into site- and scaffold-specific contributions - Zitare, Ulises Alejandro (2019)
Here we report the effect of molecular crowding on long-range protein electron transfer (ET) and disentangle the specific responses of the redox site and the protein milieu. To this end, we studied two different one-electron redox proteins that share the cupredoxin fold but differ in the metal center, T1 mononuclear blue copper and binuclear CuA, and generated chimeras with hybrid properties by incorporating different T1 centers within the CuA scaffold or by swapping loops between orthologous proteins from different organisms to perturb the CuA site. The heterogeneous ET kinetics of the different proteins was studied by protein film electrochemistry at variable electronic couplings and in the presence of two different crowding agents. The results reveal a strong frictional control of the ET reactions, which for 10 Å tunnelling distances results in a 90% drop of the ET rate when viscosity is matched to that of the mitochondrial interior (ca. 55 cP) by addition of either crowding agent. The effect is ascribed to the dynamical coupling of the metal site and the milieu, which for T1 is found to be twice stronger than for CuA, and the activation energy of protein-solvent motion that is dictated by the overall scaffold. This work highlights the need of explicitly considering molecular crowding effects in protein ET.